Dampak S-Pay Later Terhadap Konsumen Muslim: Perspektif Keuangan Islami - Hanik Fitriani (Niqosiya: Journal of Economics and Business Research, 2024)
Using the S-Pay Later digital-based payment system in the Shopee marketplace will likely make things easier for its users. Its use increases every year. This can be seen from the Financial Services Authority (OJK) records. In March 2024, debt to S-Paylater reached IDR 6.13 trillion, an increase of 2.90% from March 2023. As a Muslim consumer, it is essential to consider S-Paylater services based on perspective. Islamic finance is based on Sharia law, which contains elements of the prohibition of usury (interest), gharar (transactions must not contain elements of excessive speculation), which harm one party, may (gambling), and fairness. This research uses a qualitative descriptive method, namely by collecting literature studies, namely taking scientific references from books, journals, and other references as well as previous research that suits the researcher's problems; then, the data obtained will be analyzed to conclude. The results of this research are that the impact of S-Paylater on Muslim consumers is divided into two, namely the positive impact, including ease of accessibility and improvement of lifestyle; the negative impact is the potential for being trapped in debt, the potential for waste, compliance with sharia is still doubtful because there is an element of usury and the existence of financial entanglement.